HUBUNGAN SKALA SOMATIK DAN INTERNALIZING DENGAN GEJALA PSIKOSOMATIK PADA MAHASISWA KEDOKTERAN UPNVJ TAHUN 2022/2023 - Gusti Ayu Devania Dipta Gayatri (Gusti Ayu Devania Dipta Gayatri, 2023)
Background: During their medical education, it is not uncommon for medical students to experience stress, which can lead to psychosomatic symptoms, as they are in a phase of adaptation to their new conditions and environment. Therefore, it is necessary to conduct tests to assess the psychopathological condition of medical students, such as the MMPI test. In the MMPI test, the researcher aims to examine the somatic and internalizing scales among medical students. This study is conducted because somatic symptoms can be caused by physical illnesses or psychological problems. Thus, the objective of this research is to explore the relationship between the somatic and internalizing scales and psychosomatic symptoms among medical students at UPNVJ in the academic year 2022/2023. Method: This study adopts an analytical observational design with a cross-sectional study conducted from July 2022 to June 2023, involving a sample of 30 new medical students from UPNVJ. The simple random sampling technique is utilized, and the psychosomatic complaint scale (PCS) questionnaire and MMPI test are administered. The study employs primary data and employs Spearman correlation analysis as the statistical technique. Results: The findings indicate that the majority of respondents had high scores on both the psychosomatic and somatic scales, particularly on the NUC scale. The analysis reveals a significant correlation between the somatic scale of the MMPI and psychosomatic symptoms, with p-values of 0.02 for the Gastrointestinal Complaint (GIC) scale, 0.018 for the Head Pain Complaint (HPC) scale, and 0.002 for the Neurological Complaint (NUC) scale. However, no significant correlation is found between the internalizing scale and psychosomatic symptoms, with a p-value of 0.114 for the Anxiety Complaint (ANP) scale. Conclusion: This study demonstrates that the MMPI 180 can be used to assess psychosomatic symptoms. The somatic symptoms experienced by the body can be attributed to stress and pressure commonly encountered by medical students. It is recommended that students prevent psychosomatic symptoms by employing effective coping strategies. Keyword : MMPI, Somatic Scale, Internalizing Scale, Psychosomatic